Increased Value Added of Tuna Flakes (By-Product) from Steak Processing Through Development of Halal Commercial Food Products (Tuna Topping Spaghetti) - Latif Sahubawa; Ustadi; Leni Sophia Heliana; Rosdiana (Journal of Food and Pharmaceutical Sciences, 2021)
Yellowfin tuna is one of Indonesia's main export commodities, its meat contains high protein and can be processed into a variety of commercial food products. In the processing of loin, fillet and tuna steak, ± 10% of flaked meat is produced which can be used for processing commercial products. Spaghetti is one of the commercial products that is easily processed with raw materials and additives that are cheap and easy to obtain as well as halal and thoyib. The raw materials used are tuna flakes, spaghetti noodles and seasonings. The research objective was to analyze the chemical composition of tuna flakes and tuna topping spaghetti as well as the added value and level of consumer preference. This research uses laboratory methods, the percentage of additional selling value and consumer preferences. Proximate chemical composition of tuna flakes, namely: water content (74.80 - 75.25%); protein (16.35 - 17.00%); fat (1.43 - 1.50%); minerals (5.38 - 5.45%); carbohydrates (0.65 - 0.80%). Chemical composition of tuna topping spaghetti, namely: water content (62.73 - 69.13%); protein (7.08 - 8.34%); fat (0.42 - 0.76%); minerals/ash (0.93 - 1.16%) and carbohydrates (24.41 - 25.54%). The added value of tuna flakes in the processing of tuna topping spaghetti for two packages of spaghetti noodles (18 portions) is Rp. 147,355 (80.79%). The level of consumer preference (25 panelists) towards the visual value of tuna topping spaghetti is “very like” (76.0%) and “like” (24%); smell values, namely "really like" (72.0%) and "like" (28%); the value of taste, namely "really like" (80.0%) and "like" (20%); Texture values are “really like” (80.0%) and “like” (20%) and taste values are “really like” (76.0%) and “like” (24%).